Ethno-STEM Research Trends Through Bibliometric Analysis on Science Learning in Elementary School (Unnes Science Education Journal, 2022)
The Ethno-STEM approach has not been widely developed, while the STEM approach has developed in many countries, including Indonesia. This study aims to 1) What are the results of visualization of bibliometric mapping on Ethno-STEM learning research trends, 2) Who are the authors who play a role in Ethno-STEM research, and 3) What are the implications of Ethno-STEM in science learning in elementary school. This study uses a descriptive method with a bibliometric analysis approach based on the Google Scholar database published in 2018-2022. The results of this study indicate that the implications of Ethno-STEM learning in science learning in elementary school can improve students’ creative thinking skills by integrating HOTS (Higher Order Thinking Skill) learning models such as inquiry learning models, project based learning, and problem based learning that can support the skills of students in the 21st century.